Acute physiological changes in elite free-style wrestlers during a one-day tournament - Kafkas, M. E.; Taskiran, C.; Sahin Kafkas, A.; Özen, G.; Taskapan, Ç.; Özyalin, F.; Skarpanska-Stejnborn, A. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purpose of this study was to examine free radical production, muscle damage and inflammation responses of well-trained wrestlers to a simulated one-day tournament of free-style wrestling.